Memória e História da esquerda: a organização da massa trabalhadora em São Paulo, Brasil. // Memory and History of the Left: the organization of the working mass in São Paulo, Brazil. - Sousa, Rafael Lopes (2017)
O estudo da esquerda na cidade de São Paulo vincula-se ao estudo do movimento operário na sua versão mais consequente – a do sindicalismo. Os combates operários e a luta sindical constituíram a caixa de ressonância da organização da vanguarda revolucionária, isto é, dos partidos ou correntes que pretendiam a derrubada da ordem burguesa, anunciando a coesão social nos âmbitos dos sindicatos e dos partidos políticos nacionais. Embora incontestavelmente sob a influência de teóricos e partidos europeus, cada corrente de esquerda era prisioneira da história brasileira, da história de São Paulo e, em última instância, das relações pessoais estabelecidas entre seus quadros. Nesse sentido, as interações do PCB com o ambiente nacional, estudadas como predeterminações para muitas atividades e posições dos comunistas, devem ser acrescidas com os laços de amizade, sempre fundamentais em nossa história.The study of the left-wing party in the city of São Paulo is linked to the study of the labor movement in its more fundamental version - the syndicalism. The labor fights and the syndical struggle constituted the box of resonance of the of the revolutionary vanguard organization, that is, of the parties or movements which aspired the fall of the bourgeois order, announcing the social cohesion in the scope of the syndicates and of the national political parties. Although unquestionably under the influence of theorists and European parties, each left-wing movement was a prisoner of the Brazilian history, the history of São Paulo and, in last instance, of the personal relations established  among their participants. In this sense, the interactions of PCB with the national environment, studied as predeterminations for many activities and communist positions, must be summed to the bonds of friendship, which showed up as essential in the origins of the working class organization in our history.